The Role of Behavioral Aspects in the Implementation of the International Patient Safety Goals to Reduce the Risk of Patient Falls in Hospitals: A Scoping Review - Indriyani Indriyani; Zahroh Shaluhiyah; Daru Lestantyo (Universitas Pahlawan Tuanku Tambusai, 2026)
Nurses represent the largest proportion of healthcare professionals in hospitals (40–60%) and are entrusted with the continuous implementation of patient fall prevention measures. Accordingly, they hold a critical role in influencing the success of hospital accreditation. Tujuan: Penelitian ini bertujuan untuk melakukan tinjauan literatur guna mengidentifikasi bukti ilmiah terkini mengenai faktor-faktor risiko jatuh pasien serta efektivitas berbagai intervensi pencegahan yang diterapkan di fasilitas pelayanan kesehatan. Metode: Penelitian menggunakan desain scoping review yang direncanakan melalui penelusuran artikel ilmiah pada basis data ScienceDirect, dengan kata kunci